Determination of major phenolic acids, phenolic diterpenes and triterpenes in Rosemary (Rosmarinus Officinalis L.) by gas chromatography and mass spectrometry - Islamčević Razboršek, Maša (Acta chimica slovenica, 2007)
A gas chromatographic-mass spectrometric (GC-MS) method for the simultaneous identification and quantification of seven major phenolic and terpenic compounds in Rosmarinus officinalis L. was developed. The compounds were identified as trimethylsilyl (TMS) derivatives of phenolic acids (caffeic and rosmarinic acid), phenolic diterpene (carnosic acid), and pentacyclic triterpenes (ursolic, oleanolic, betulinic acid and betulin). These compounds have been identified by retention time and comparison of mass spectra. The procedure involves ultrasonic extraction using solvent mixture of tetrahydrofuran and ethanol. Extracts were fractionated by size exclusion chromatography (SEC) after purifying on graphitised carbon. The fraction with phenolic and terpenic compounds was derivatised prior to GC-MS analysis using N-methyl-N-trimethylsilyl trifluoroacetamide (MSTFA) as a derivatisation reagent. The derivatisation process was optimized regarding temperature and reaction time. The linearity of the method was tested in concentration range 4-25 mg L-1. The correlation coefficients (r2) were in the range of 0.997 to 0.999. The average recoveries for all compounds ranged from 80 to 82%. The GC-MS technique is specific and sensitive, and can be used for simultaneous identification and determination of a wide range of phenolic and terpenic compounds in different plants even at trace levels.
Keywords: analizna kemija; analizne metode; diterpeni; masna spektrometrija; plinska kromatografija; rožmarin; triterpeni